2022
DOI: 10.1542/peds.2021-053600
|View full text |Cite
|
Sign up to set email alerts
|

Validating a Sclera-Based Smartphone Application for Screening Jaundiced Newborns in Ghana

Abstract: OBJECTIVES: Reducing the burden of bilirubin-induced neurologic complications in low-resource countries requires reliable and accessible screening tools. We sought to optimize and validate a sclera-based smartphone application, Neonatal Scleral-Conjunctival Bilirubin (neoSCB), for screening neonatal jaundice. METHODS: Using a cross-sectional design, consecutive eligible infants (aged 0–28 days, in the hospital, not critically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Several of the included studies conducted comparisons between the accuracy of Transcutaneous Bilirubin (TcB) and MAPB in their respective study cohorts. These investigations consistently favored TcB over MAPB in the estimation of TSB values ( 205 207 ). The reported correlations between TcB and TSB exhibited a range from 0.77 to 0.97, with the highest concordance observed in neonates during their initial hospitalization and the lowest in outpatient settings, where MAPB measurements are anticipated for employment ( 122 , 130 , 161 , 219 220 ).…”
Section: Non-invasive Approaches For Jaundice Screening and Their Lim...mentioning
confidence: 66%
See 1 more Smart Citation
“…Several of the included studies conducted comparisons between the accuracy of Transcutaneous Bilirubin (TcB) and MAPB in their respective study cohorts. These investigations consistently favored TcB over MAPB in the estimation of TSB values ( 205 207 ). The reported correlations between TcB and TSB exhibited a range from 0.77 to 0.97, with the highest concordance observed in neonates during their initial hospitalization and the lowest in outpatient settings, where MAPB measurements are anticipated for employment ( 122 , 130 , 161 , 219 220 ).…”
Section: Non-invasive Approaches For Jaundice Screening and Their Lim...mentioning
confidence: 66%
“…In a collaborative clinical pilot, researchers conducted comprehensive studies on neonatal jaundice screening utilizing smartphone technology. The pilot involved 37 newborns at University College Hospital London, and a year-long study was carried out on 724 newborns in Ghana ( 207 ). To capture precise eye images, the research team employed a Samsung Galaxy SB smartphone, capturing two images per infant's eye—one with the LED flash activated and one without, effectively mitigating ambient light influence through ambient subtraction techniques.…”
Section: Non-invasive Approaches For Jaundice Screening and Their Lim...mentioning
confidence: 99%
“…Their reliability in populations with more pigmented skin has not been tested widely (19)(20)(21) represents an initial insurmountable investment for most constrained-resource settings, but other transcutaneous devices might be as accurate and more affordable (24). Other cheaper screening tools have been tested, such as icterometers (25,26) and phone-based apps (27)(28)(29), and when properly evaluated could be used by health workers at birthing centers and in remote settings, and even by parents (30) after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in China demonstrated decreased neonatal readmission rate and decreased maternal anxiety scores for mother-infant dyads that used a smartphone app to monitor for neonatal jaundice at home under web-based guidance of pediatricians compared to the control group that received routine care ( 108 ). Similar smartphone-based detection tools are being studied in other regions of the world, including Singapore ( 109 ), Ghana ( 110 ), and Saudi Arabia ( 111 ), and Nigeria ( 112 ), just to name a few. Although these tools are best suited as screening devices, as with the TcB, they are encouraging uses of state-of-the-art technology to improve the recognition and diagnosis of NJ.…”
Section: Opportunities For Future Stepsmentioning
confidence: 99%